Food Insecurity and Cardiometabolic Risk among Turkish Adults: A Cross-Sectional Study - Bozdemir, Esra; Yuksel, Aysun (Jurnal Gizi dan Pangan, 2024)
This study examined 175 volunteers aged 18‒64 to explore the connection between food insecurity and anthropometric measurements, diet quality scores and cardiometabolic risk factors. The design of the study is cross-sectional, and the data were obtained using a number of questionnaires applied to individuals who visited the diet clinic. Participants' diet quality was assessed using the Healthy Eating Index-2015 (HEI-2015) and food security was evaluated using the Household Food Insecurity Access Scale. Cardiometabolic risk factors were determined based on HEI-2015 scores, Body Mass Index (BMI), waist circumference, waist/height ratio, physician-diagnosed diabetes, hypertension, dyslipidemia, regular physical activity status, and smoking habits. As a result of the study, 41.1% of the participants were found to be food-insecure, and 77.8% had diet quality that needed improvement. The average BMI value of food-insecure women was found to be higher than that of food-secure women (32.37±7.77 kg/m2 and 29.86±5.22 kg/m2, respectively) (p=0.003). Furthermore, food-insecure women had a higher average waist circumference (p=0.001). A significant negative relationship was determined between BMI value, waist circumference and waist/height ratio, which are among the cardiometabolic risk factors, and food insecurity.